PROBLEMATIKA KEWENANGAN PENETAPAN TERSANGKA ANGGOTA TNI OLEH KOMISI PEMBERANTASAN KORUPSI - Jamaludin, Ahmad (Universitas Muhammadiyah Ponorogo, 2024)
In its growth, corruption continues to be a problem and an enemy for the nation and state. Corruption is now not only committed by civilian officials and corporate parties, but can also be committed by the military, in this case the Indonesian National Army. In the process, it is possible for conflicts of authority to occur, including the recent case of the Corruption Eradication Commission's Hand Capture Operation at the National Search and Rescue Agency related to the determination of corruption case suspects involving two active military members. This research aims to find out the authority of the Corruption Eradication Commission in determining suspects who are active military members and the legal consequences of this determination. Normative juridical methods through literature studies were used in this research which shows that if viewed juridically, the Corruption Eradication Commission has the authority to determine suspects even up to the prosecution stage because the laws that form their basis are more specific than laws related to the military when viewed from the perspective of the lex specialist systematics principle. Determining a suspect is legal as long as coordination has been carried out because legally this institution has the authority to control corruption cases based on article 42 of the Corruption Eradication Committee Law as well as article 65 (2) of the TNI Law. However, to avoid misperceptions like this happening again, it seems necessary to revise the Military Justice Law and strengthen the Corruption Eradication Commission Law to make law enforcement more efficient in criminal acts of corruption.